THE EFFECTS OF PHYSICAL THERAPY INTERVENTIONS ON FATIGUE MANAGEMENT IN CANCER SURVIVORS - Othman Mohammed Sahli, Misfer Abdullh Muokaerk Doseri, Eyad Ibrahim Mobarki, Nasser Ali Alhmdan, Abdullah Raad Abdullah Alruaydan, Abdullah Saleh Khmeri Alonazi; Abdulaziz Ibrahim Bahni Almadhri, Latefa Moubark Alhoumid, Mohammad Ahmad Mohammad Sharahily, Saad Naem Abdullah Alshehri, Abdulrahman Ibrahim Mohammed Almubarak; Ahmed Mohammed Abdullah Kulaybi, Khulood Ahmed Bader, Waad Saad Alfahad, Eyad Ibrahim Mobarki, Rami Ayesh Alanazi, Mohammed Hussain Ahmed Alyami (Chelonian Research Foundation, 2022)
The main objective of this systematic review is to organize the existing data on physical exercise regimens and their impact on (1) physical performance results, (2) reported tiredness, and (3) quality of life (QoL) in patients undergoing first therapy for breast cancer. A comprehensive literature search, following the PRISMA criteria, was conducted utilizing four databases (Web of Science, Cochrane Library for Clinical Trials, PubMed, and Medline). The chosen studies were assessed for their methodological quality, and information about physical performance, quality of life, and weariness was collected. Twenty-eight randomized controlled trials (RCTs) were included. The study found several treatment methods used during the first treatment, including radiation therapy, chemotherapy, and combination therapy. Additionally, many forms of physical training treatments were discovered, such as aerobic endurance exercise, strengthening programs, or a combination of both. Consequently, the findings were organized into clusters based on the indicated grouping. This included identifying all important outcomes linked to physical performance (such as 6-minute walk test or peak oxygen uptake), quality of life (measured by surveys), and tiredness (also assessed through questionnaires). Various fitness routines are accessible for rehabilitating breast cancer patients during adjuvant treatment. In general, engaging in resistance training alone or combining it with cardiovascular endurance training yields optimal outcomes, particularly in terms of physical performance and perceived exhaustion. Keywords: Physical therapy, breast cancer, review, treatment, interventions.